A Multidimensional Poverty Analysis In Madura Island, 2023 - Wedi Musta Mulari; Rudi Purwono (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This quantitative study aims to analyze the determinants that influence the probability of multidimensional poverty among households on Madura Island in 2023. Using SUSENAS data and the Alkire-Foster (AF) Method, this study confirms that the multidimensional poverty rate in this region remains high. Logistic Regression Analysis identified key factors: Non-Cash Food Assistance (BPNT) proved to be significant and negative, confirming its effectiveness as a social safety net. The most crucial finding is the role of access to formal financial services (People's Business Credit and Cooperative Credit), which significantly and negatively affects the probability of multidimensional poverty, making it the most vital determinant in reducing deprivation. In addition, the marital status of the head of household (KRT) has a negative and significant effect, while the number of household members has a positive but insignificant effect. In conclusion, to overcome multidimensional poverty in Madura in the post-pandemic period, policies must focus efforts on massively expanding access to KUR and Cooperative Credit as an effective and sustainable economic empowerment strategy, while maintaining the continuity of social assistance.